2021
DOI: 10.1136/gutjnl-2021-324109
|View full text |Cite
|
Sign up to set email alerts
|

GM-CSF drives myelopoiesis, recruitment and polarisation of tumour-associated macrophages in cholangiocarcinoma and systemic blockade facilitates antitumour immunity

Abstract: ObjectiveIntrahepatic cholangiocarcinoma (iCCA) is rising in incidence, and at present, there are limited effective systemic therapies. iCCA tumours are infiltrated by stromal cells, with high prevalence of suppressive myeloid populations including tumour-associated macrophages (TAMs) and myeloid-derived suppressor cells (MDSCs). Here, we show that tumour-derived granulocyte–macrophage colony-stimulating factor (GM-CSF) and the host bone marrow is central for monopoiesis and potentiation of TAMs, and abrogatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 42 publications
2
31
2
Order By: Relevance
“…We next examined the expression of well-known genes related to macrophage recruitment and polarization, including CCL2, CCL3, CCL4, CCL5, CSF1, CSF2 and IL6 [ 15 , 17 , 18 ]. The mRNA expression of CCL3, CCL4 , and CSF1 was significantly upregulated in IL17D –expressing A549 cells compared with that in control cells ( Figure 4A ), whereas IL17D overexpression in the murine lung cancer cell line LLC1 increased Ccl3, Ccl4 , and Il6 expression ( Figure 4B ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We next examined the expression of well-known genes related to macrophage recruitment and polarization, including CCL2, CCL3, CCL4, CCL5, CSF1, CSF2 and IL6 [ 15 , 17 , 18 ]. The mRNA expression of CCL3, CCL4 , and CSF1 was significantly upregulated in IL17D –expressing A549 cells compared with that in control cells ( Figure 4A ), whereas IL17D overexpression in the murine lung cancer cell line LLC1 increased Ccl3, Ccl4 , and Il6 expression ( Figure 4B ).…”
Section: Resultsmentioning
confidence: 99%
“…According to previous reports, IL-17D can induce endothelial cells to express IL-6, IL-8, and GM-CSF, which are involved in the differentiation and recruitment of myeloid cells in the TME [15][16][17]. To investigate the role of IL-17D in the immune microenvironment of lung cancer, we used flow cytometry to characterize the tumor-infiltrating immune cells in a subcutaneous tumor model of IL17D-expressing LLC1 cells.…”
Section: Il-17d Promotes Infiltration Of Tumor-associated Macrophages...mentioning
confidence: 99%
“…For example, neutralization of GM-CSF prevented MDSC accumulation and abrogated HCC progression (181). More recently, the aGM-CSF antibody was found to reprogram the tumor microenvironment from immunosuppressive to anti-tumorigenic in intrahepatic cholangiocarcinoma by reducing the expression of ARG1 and PD-L1 in granulocytes and monocytes, inhibiting M2 TAMs, and augmenting activation and tumor-infiltration of CD8 + T cells, leading to a pan-myeloid repolarization towards the proimmunogenic, anti-tumor phenotype (182). Similar paradigms of restoration of tumor immunosurveillance using anti-GM-CSF antibodies to neutralize GM-CSF secreted by breast cancer cells have been demonstrated by Su et al (183).…”
Section: Overcoming the Pro-tumorigenic Functions Of Gm-csf During Ca...mentioning
confidence: 99%
“…Overall, TAMs mainly plays a role in promoting cancer in CCA. In order to inhibit the tumor-promoting effect of M2 macrophages, Ruffolo et al built an orthotopic tumor-bearing mouse model of ICC and confirmed that anti-GM-CSF monoclonal antibody treatment can reverse tumor-induced M2 polarization of TAMs, thus stimulating the immune activity of T cells and preventing the establishment of an immunosuppressive microenvironment [99]. TAMs are meaningful markers in evaluating the clinical prognosis of patients with ICC [100].…”
Section: Macrophages In Ccamentioning
confidence: 99%